Spillover effects in environmental behaviors, across time and context: a review and research agenda. Issue 4 (21st April 2017) - Nilsson, Andreas; Bergquist, Magnus; Schultz, Wesley P.
Abstract: When implementing environmental education and interventions to promote one pro-environmental behavior, it is seldom asked if and how non-target pro-environmental behaviors are affected. The spillover effect proposes that engaging in one behavior affects the probability of engagement or disengaging in a second behavior. Therefore, the positive spillover effect predicts that interventions targeting one specific behavioral have the capacity to promote non-targeted and/or future pro-environmental behaviors. However, the negative spillover effect predicts that engaging in a first pro-environmental behavior will prevent or decrease a second pro-environmental behavior. Since the theoretical and empirical basis for positive and negative spillover effects are not sufficiently understood, the present paper (1) suggests a distinction between behavioral, temporal, and contextual spillovers (2) reviews the existing spillover research literature across a variety of environmental domains, (3) presents potential moderators governing the direction of spillover effects, and finally (4) discuss techniques to promote pro-environmental spillovers.